Evaluation of the Concentrations of Nitrate, Nitrite and Heavy Metals in Spinach (Spinacia oleracea) Irrigated along the Amba Stream Lafia, Nasarawa State (Lafia Journal of Scientific and Industrial Research, 2024)
The concentrations of nitrate, nitrite and heavy metals were evaluated in the soil and edible portion of Spinach, irrigated along the Amba stream, Lafia, Nasarawa State. Nitrate, nitrite and heavy metals in the soil and spinach samples were determines using Spectrophotometric method. The mean concentrations (± Standard deviation) of nitrate ranged from 3042.91±1.62mgkg-1 to 4977.26±9.57mgkg-1, for Spinach while 5899.20±58.98mgkg-1 to stipulated by WHO and EC respectively. Mean of nitrite concentrations (NO2) (± standard deviation) ranged from 0.00029±0.00002mgkg-1 to 00102±0.00001mgkg-1 for all the spinach, while 0.00332±0.00002mgkg-1 to 0.00903±0.00002mgkg-1 for all soil were all below the mg/kg maximum specified by WHO. NO3 levels were generally higher than NO2.The mean concentrations of heavy metals ranged from Cd (1.29±0.01 mg/kg) to Fe (281.60±1.65 mgkg-1) for spinach while Cd (0.93±0.32 mgkg-1) to Fe (1084.1±1.73 mgkg-1) for soil. The values in spinach exceeded the permissible limit set by FAO. Transfer factors for the anions between the soil and spinach identify the efficiency of a spinach species to accumulate a given anion. There was positive correlation at p = 0.05 between the anions in the spinach. The transfer factors calculated were lower for all metals except cadmium (1.39).